2020
DOI: 10.1371/journal.pone.0225267
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide analysis of gene expression changes in skin from patients with type 2 diabetes

Abstract: Non-healing chronic ulcers are a serious complication of diabetes and are a major healthcare problem. While a host of treatments have been explored to heal or prevent these ulcers from forming, these treatments have not been found to be consistently effective in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 109 publications
3
13
0
Order By: Relevance
“…An animal study showed that LRP1 expression was increased in cardiomyocytes isolated from acutely diabetic rats [22]. Other studies reported the upregulation of LRP1 in epicardial fat and skin from diabetic patients compared with control individuals, which was consistent with our findings [23,24]. In contrast, another study showed a significant reduction in LRP1 expression in subjects with diabetic peripheral neuropathy compared with the noncomplication group [25].…”
Section: Discussionsupporting
confidence: 90%
“…An animal study showed that LRP1 expression was increased in cardiomyocytes isolated from acutely diabetic rats [22]. Other studies reported the upregulation of LRP1 in epicardial fat and skin from diabetic patients compared with control individuals, which was consistent with our findings [23,24]. In contrast, another study showed a significant reduction in LRP1 expression in subjects with diabetic peripheral neuropathy compared with the noncomplication group [25].…”
Section: Discussionsupporting
confidence: 90%
“…In general terms, the differential global gene expression in the skin of the diabetic humanized mice (D0vsC0) closely reproduced the cutaneous transcriptome profiling in diabetic patients [ 37 , 38 ]. Specifically, those studies showed altered GO_BPs and KEGG pathways related to focal adhesions, cell adhesions mediated by integrins, and ECM-related processes, as in our diabetic skin-humanized mouse model ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 90%
“…Takematsu et al examined the changes in gene expression in the skin between 13 patients with type 2 diabetes and 14 non-diabetic patients. 33 They found that the most upregulated genes included three lncRNAs: LINC01118, RP11545I5.3, and an unknown lncRNA. In contrast, the most downregulated genes included three lncRNAs: LINC01060, HPRT1P2, and CCNYL3.…”
Section: Lncrna Expression Profiling In Diabetic Foot Ulcersmentioning
confidence: 99%